(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article has considered the structure of the concept, the specifics of its figurative component. The Galician-Russian proverbs that describe intellectual activity of person have been analyzed; the specific features of Ukrainian ethnic consciousness in the diachronic aspect have been defined. Proverbs that represent the concept ’mind’ at a certain synchronic interval have been researched in the article.